On the inverse problem for perturbations of an abstract wave equation in the Lax-Phillips scattering scheme - Kuzhel', S. A. (Ukrains’kyi Matematychnyi Zhurnal, 2000)
The inverse scattering problem for perturbations of an abstract wave equation is investigated within the framework of the Lax-Phillips scattering scheme.